2016
DOI: 10.1007/s11427-016-5010-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of non-coding RNAs in epigenetic regulation

Abstract: Recent deep sequencing surveys of mammalian genomes have unexpectedly revealed pervasive and complex transcription and identified tens of thousands of RNA transcripts that do not code for proteins. These non-coding RNAs (ncRNAs) highlight the central role of RNA in gene regulation. ncRNAs are arbitrarily divided into two main groups: The first includes small RNAs, such as miRNAs, piRNAs, and endogenous siRNAs, that usually range from 20 to 30 nt, while the second group includes long non-coding RNAs (lncRNAs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Non-coding RNAs are classified according to their length, with those less than 200 nucleotides (nt) being classified as microRNAs, while the remainder are lncRNAs19. lncRNAs were initially believed to have no biological function, but recent studies have suggested that they are widely involved in X-chromosome silencing, genomic imprinting, chromatin modification, transcriptional activation, interference, nuclear transport and other important regulatory processes20212223. By RNA sequencing (RNA-seq) technology and bioinformatic analysis, thousands of lncRNAs have been discovered in organisms from fruit flies to humans and their functions have been predicted.…”
mentioning
confidence: 99%
“…Non-coding RNAs are classified according to their length, with those less than 200 nucleotides (nt) being classified as microRNAs, while the remainder are lncRNAs19. lncRNAs were initially believed to have no biological function, but recent studies have suggested that they are widely involved in X-chromosome silencing, genomic imprinting, chromatin modification, transcriptional activation, interference, nuclear transport and other important regulatory processes20212223. By RNA sequencing (RNA-seq) technology and bioinformatic analysis, thousands of lncRNAs have been discovered in organisms from fruit flies to humans and their functions have been predicted.…”
mentioning
confidence: 99%
“… 44 As different RBPs tend to associate with one another to form various macromolecular complexes, each RBP in the complex may uniquely contribute to RNA code recognition, thus generating a combinational RNA code to institute the complex specificity observed in the cell. 55 The AID “mutator complex” may contain other proteins that indirectly interact with AID, 56 , 57 including several hnRNP proteins that work together with ROD1 to restrict AID targeting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, possible roles of non-coding RNAs, which can be derived from pseudogenes, in epigenetic regulation (e.g. histone modification and chromatin remodeling) still remain an open question (Chen and Xue, 2016).…”
Section: Discussionmentioning
confidence: 99%